1996
DOI: 10.1111/j.1476-5381.1996.tb15746.x
|View full text |Cite
|
Sign up to set email alerts
|

Regionally different N‐methyl‐D‐aspartate receptors distinguished by ligand binding and quantitative autoradiography of [3H]‐CGP 39653 in rat brain

Abstract: Binding of D,L-(E)-2-amino-4-[3H]-propyl-5-phosphono-3-pentenoic acid ([3H]showed that the inhibition was lower in striatum (72% of control), with respect to cortex (66% of control) and hippocampal formation (58% of control).6 The inhibitory action of 10 gM glycine was reversed by 100 gM 7-chloro-kynurenic acid (7-CKA), a competitive antagonist of the glycine site of the NMDA receptor channel complex, in all areas tested. Moreover, reversal by 7-CKA was not the same in all regions (P<0.05, two-ways ANOVA). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…The enhancement was uneven in rat brain: in CPu, for example, the increase was higher than in the cerebral cortex. This was in line with the previous ®nding that 1 mM glycine was able to inhibit basal [ 3 H]-CGP39653 binding to a smaller extent in CPu than in the cerebral cortex (Mugnaini et al, 1996).…”
Section: British Journal Of Pharmacology Vol 132 (8)supporting
confidence: 80%
See 3 more Smart Citations
“…The enhancement was uneven in rat brain: in CPu, for example, the increase was higher than in the cerebral cortex. This was in line with the previous ®nding that 1 mM glycine was able to inhibit basal [ 3 H]-CGP39653 binding to a smaller extent in CPu than in the cerebral cortex (Mugnaini et al, 1996).…”
Section: British Journal Of Pharmacology Vol 132 (8)supporting
confidence: 80%
“…The extent of this eect diered between regions and revealed the existence of NMDA receptor subtypes which may have a dierent sensitivity to endogenous ligands as well as to potential therapeutic agents (Mugnaini et al, 1996). The aim of the present study was to con®rm these ®ndings in rat brain and look for the possible existence of similar NMDA receptor subtypes in human brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the difference between intact and ovariectomized rats observed in the hippocampus is supported by the recent finding that NMDA receptor changes during the estrous cycle (Lu et al 2000). So far, it has been shown that specific L-[ 3 H]CGP 39653 binding is possible only when subunit NMDA receptor 2A is present in the heteromeric receptor (Marti et al 1993;Lynch et al 1994;Laurie and Seeburg 1994;Mugnaini et al 1996).…”
Section: Nmda Receptors Mrna Levelsmentioning
confidence: 99%